Dietary nitrate does not modify blood pressure and cardiac output at rest and during exercise in older adults: a randomised cross-over study. (2nd January 2018) - Oggioni, C.; Jakovljevic, D. G.; Klonizakis, M.; Ashor, A. W.; Ruddock, A.; Ranchordas, M.; Williams, E.; Siervo, M.
Abstract: Dietary nitrate (NO3 - ) supplementation has been associated with improved vascular and metabolic health. We conducted a double-blind, cross-over, placebo-controlled RCT to investigate the effects of 7-d consumption of beetroot juice compared with placebo on (1) blood pressure (BP) measured in resting conditions and during exercise, (2) cardiac and peripheral vascular function and (3) biomarkers of inflammation, oxidative stress and endothelial integrity. Twenty non-smoking healthy participants aged 60–75 years and BMI 20.0–29.9 kg/m 2 were recruited. Measurement was conducted before and after each 7-d intervention period. Consumption of NO3 -  had no effect on resting systolic and diastolic BP. NO3 -  consumption did not improve indexes of central and peripheral cardiac function responses during cardiopulmonary exercise testing. Dietary NO3 -  supplementation did not modify biomarkers of inflammation, oxidative stress and endothelial integrity. This study does not support the short-term benefits of dietary NO3 -  supplementation on physiological and biochemical markers of vascular health in older healthy adults. Graphical Abstract: